Improvisation for technically-oriented peoples - McMahon, Russell (2019)
Teaching “soft” skills to technical people is just as important as learning “hard” skills. Improvisation techniques can also be used in teaching technical concepts such as cybersecurity, agile development, database design, programming concepts, and most importantly how to better one’s communication skills. In an age where rapid changes have become the norm, improvisation techniques can be used to help navigate the new challenges of the next generation careers, global interaction, and technologies. These techniques can easily be incorporated in other methodologies such as creative problem-solving and design thinking. There are clearly defined and flexible rules for improvising, which make it easier for technical persons to learn and use in their daily life and career.